1987
DOI: 10.1152/jappl.1987.62.3.1331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on tracheal mucociliary clearance in beagle dogs

Abstract: Tracheal mucous velocity measurements were made in 24 beagle dogs in five age groups, using a gamma camera to detect movement of instilled 99mTc-macroaggregated albumin. Age groups were defined as immature (9-10 mo), young adult (2.8-3.0 yr), middle aged (6.7-6.9 yr), mature (9.6-9.8 yr), and aged dogs (13.6-16.2 yr). Mean velocities were 3.6 +/- 0.4 (SE) mm/min in the immature dogs, 9.7 +/- 0.6 mm/min in the young adults, 6.9 +/- 0.5 mm/min in the middle-aged dogs, 3.5 +/- 0.8 mm/min in the mature dogs, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…' Group C, dogs with no clinical signs of respiratory disease, situs solitus and normal ultrastructure of nasal cilia that were born from matings between presumed heterozygotes of ICS. Whaley et al [1987]. '' Less than 10% cilia had any motility, and beat was random.…”
Section: Resultsmentioning
confidence: 99%
“…' Group C, dogs with no clinical signs of respiratory disease, situs solitus and normal ultrastructure of nasal cilia that were born from matings between presumed heterozygotes of ICS. Whaley et al [1987]. '' Less than 10% cilia had any motility, and beat was random.…”
Section: Resultsmentioning
confidence: 99%
“…In healthy dogs, thoracic radiographic findings (Reif and Rhodes, 1966) and tracheobronchial mucociliary clearance (Whaley et al, 1987) are known to be age dependent. One study of 18 Beagle dogs of various ages reported no age-related changes in total and differential cell counts (TCC and DCC) in bronchoalveolar lavage fluid (BALF) (Mayer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in the tracheal mucus velocity between groups of dogs of different ages were noted. In the course of maturation and ageing, mucus velocity rises exponentially to peak values in young adult dogs and declines linearly thereafter 18 . In mice exposed to inhalation of kaolin conveyed by cigarette smoke, the most severe changes in the pulmonary parenchyma and ultrastructure of alveolar macrophages were recorded in groups of older animals.…”
Section: Discussionmentioning
confidence: 97%